Identifying functional regions of rRNA by insertion mutagenesis and complete gene replacement in Tetrahymena thermophila. - Sweeney, R (1989)
The free, linear macronuclear ribosomal RNA genes (rDNA) of Tetrahymena are derived from a unique copy of micronuclear rDNA during development. We have injected cloned copies of the micronuclear rDNA that have been altered in vitro into developing macronuclei and obtained transformants that express the paromomycin-resistant phenotype specified by the injected rDNA. In most cases, these transformants contain almost exclusively the injected rDNA which has been accurately processed into macronuclear rDNA. Mutants with a 119 bp insertion at three points in the transcribed spacers and at two points in the 26S rRNA coding region were tested. Cells containing these spacer mutant rDNAs are viable, although one of them grows slowly. This slow-growing line contains the insertion between the 5.8S and 26S rRNA coding regions and accumulates more rRNA processing intermediates than control lines. One of the 26S rRNA mutants failed to generate transformants, but the other did. These transformants grew normally, and produced 26S rRNA containing the inserted sequence. A longer insertion (2.3 kb) at the same four points either abolished transformation or generated transformants that retained at least some wild-type rDNA. This study reveals that some rRNA sequences can be altered without significantly affecting cell growth.